IMPLEMENTASI PRINSIP KEHATI-HATIAN DALAM PERJANJIAN KREDIT MELALUI AFLIKASI PAY LATER - Husnaini, Husnaini (Justici, 2024)
ABSTRACT Discussing fintech is not far from the development of e-commerce, business competition in the digital world is increasingly high, people prefer to shop or make transactions via applications. The two applications depend on each other to provide the best services and facilities for their users. This is what makes fintech applications develop financial technology features to become more varied. For example, the availability of short-term financing or commonly known as PayLater. The research method that the author uses in this research is normative legal research. Normative research is something that is done by studying, examining problems, and exploring or examining the norms and rules that apply in relation to the problem being researched. The regulations are contained in the Financial Services Authority Circular Letter Number 18/SEOJK.02/2017 concerning Information Technology Risk Management and Governance in Information Technology-Based Money Lending and Borrowing Services in Chapter V in paragraph 4 letter a.